(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article examines and gives the preliminary analysis of newly discovered ancient Turkic writing, which was discovered by local resident during the archeological expeditions in 2012 in East Kazakhstan region. The text of transcription consist of 8 symbols; the rough translation from the ancient Turkic is: Er atïm Taγran .... š? – My heroic name Tagran ..... u? The preliminary analysissuggests that the inscription refers to the On ok period, Türgesh era of VIII-IX centuries. Tamga-sign graphics are presumably close to those of Talas monuments.